Social mobilization, global capitalism and struggles over food: a comparative study of social movements - Campos Motta, Renata (Entangled inequalities: exploring global asymmetries, 2016)
Theorizing and research disputes over GMOs -- A silenced revolution (1996-2002) -- Increasing noise (2003-2013) -- The unexpectedly contentious Brazilians (1996-2002) -- The politics of faits accomplis (2003-2013) -- Many tales of GMOs: a comparison -- Conclusions